Coming to the fore: The audibility of women’s sexual pleasure in popular music and the sexual revolution - Stratton, Jon (Cambridge University Press, 2014)
This paper examines the genre of tracks centred around the mid-1960s to the mid-1970s which include aural representations of female sexual pleasure. The two most important tracks, and the ones on which this paper focuses, are Jane Birkin and Serge Gainsbourg ‘Je t’aime . . . moi non plus’ and Donna Summer ‘Love To Love You Baby’. The paper argues that this new audibility of female sexual pleasure related to the transformation in the understanding of female orgasm associated with Alfred Kinsey and with William Masters and Virginia Johnson, the American sexologists who radically changed Western understandings of sexual behaviour in the 1950s and 1960s. More broadly, the paper argues for a link between the so-called sexual revolution of the late 1960s and 1970s and the popularity of tracks in which sounds identified as female sexual pleasure were upfront in the musical mix.